Ferulic acid derivatives inhibiting Staphylococcus aureus tetK and MsrA efflux pumps - Patrícia Gonçalves Pinheiro (2022)
Background: Bacterial resistance to multiple drugs has recently emerged as a serious health problem. Concomitantly, the characterization of new substances with potential antimicrobial activity has been less frequent in the drug development industry. The overexpression of genes encoding efflux pumps that expel antimicrobial drugs from the intracellular environment, lowering these to subinhibitory concentrations, are among the resistance mechanisms predisposing microorganisms to high drug resistance. Staphylococcus aureus is a bacterium found in the normal microbiota of the skin and mucous membranes, and is an opportunistic microorganism capable of causing infections with high rates of morbidity and mortality. TetK is an efflux pump characterized by its ability to provide bacterial resistance to antibiotics from the tetracycline class. This study aimed to evaluate the inhibitory effect of ferulic acid and four of its esterified derivatives against resistant Staphylococcus aureus strains. Method: Ferulic acid derivatives were obtained by esterification and then characterized by hydrogen and carbon-13 nuclear magnetic resonance analysis. The minimum inhibitory concentrations (MIC) of ferulic acid and its esterified derivatives, ethidium bromide, and antibiotics were obtained using the microdilution test, while the efflux pump inhibition test was conducted by examining reduction in the MICs. Results: Propylferulate was seen to reduce the minimum inhibitory concentration (MIC) of both the control substance ethidium bromide and the tested antibiotic, indicating that this compound is promising for the use of efflux pump inhibition of IS-58 strains. Conclusions: This study provides strong evidence that the molecular basis for this activity is potentially due to the MsrA and TetK efflux pumps. However, further investigations are necessary to prove this hypothesis and elucidate the potentiating mechanism of the modulatory effect.